KORELASI KETERAMPILAN MENYIMAK WAWANCARA DENGAN KETERAMPILAN MENULIS TEKS BERITA SISWA KELAS VIII SMP NEGERI 23 PADANG - Permatasari, Intan; Nursaid, Nursaid (Universitas Negeri Padang, 2019)
ABSTRACT The purpose of this study is three. First, describe the listening skills of class VIII interview at SMP Negeri 23 Padang. Second, describing the news text writing skills of class VIII students of SMP Negeri 23 Padang. Third, describe the correlation of listening skills to interviews with news text writing skills of class VIII students of SMP Negeri 23 Padang. This type of research is a quantitative descriptive method. The design used in this study is correlational design. The population of this study was Class VIII of SMP Negeri 23 Padang. The sample in this study was determined by proportional random sampling of 25% of the population, namely 51 students. The research data were test scores on interview listening skills and news text writing skills test scores. The research instrument was an objective test to measure interview listening skills and performance tests to measure news text writing skills. The results of this study are three. First, the writing text skills of class VIII students of SMP Negeri 23 Padang are in more than enough qualifications. Secondly, listening to interview skills is more than adequate. Third, listening skills interviewed were correlated at 7,41 with news text writing skills of class VIII students of SMP Negeri 23 Padang. Kata Kunci: Korelasi, Keterampilan Menyimak Wawancara, Keterampilan Menulis Teks Berita